DESCRIPTION OF STUDENTS' BEHAVIOR AT SDN 005 SUNGAI KUNJANG IN ACCESSING PORNOGRAPHIC SITES (CASE STUDY) - Ramadhan, Fitri; Ardyanti, Dian; Rahayu, Eka Putri (STIKes Medistra Indonesia, 2025)
Pornography is one of the negative behaviors carried out by teenagers because of the ease of accessing pornographic content plus the high curiosity of teenagers, the behavior of accessing pornographic sites is still something that must be considered, the habit of accessing pornographic sites on the internet can cause negative things. The purpose of this study was to determine the description of the behavior of students at SDN 005 Sungai Kunjang. This type of research is qualitative research with a case study research design. This study was conducted with in-depth interviews and observations. The research sample aimed at 6 informants at SDN 005 Sungai Kunjang Samarinda which were determined by purposive sampling techniques. This study shows that school students start accessing pornography at an early age. In the predisposing factors, teenagers have less knowledge with a high sense of curiosity and a positive attitude that forms the behavior of accessing pornography. In supporting factors, students access because they are curious and do not use their free time properly with the guidance of parents and schools to provide limits to students. In the driving factors, peers greatly influence accessing pornography while teachers are also expected to continue guidance to prevent pornography in schools. The existence of predisposing, supporting and driving factors that influence the occurrence of behavior in accessing pornographic sites. It is expected that parents and schools improve policies and guidance for students to prevent pornography. Students are expected to follow directions and guidance to reduce access to pornography.